Effects of Prenatal Exposure to Alcohol and Smoking on Fetal Heart Rate and Movement Regulation - Lucchini, Maristella; Shuffrey, Lauren C.; Nugent, J. David; Pini, Nicoló; Sania, Ayesha; Shair, Margaret; Brink, Lucy; du Plessis, Carlie; Odendaal, Hein J.; Nelson, Morgan E.; Friedrich, Christa; Angal, Jyoti; et al. (Frontiers in Physiology, 2021)
Negative associations of prenatal tobacco and alcohol exposure (PTE and PAE) on birth outcomes and childhood development have been well documented, but less is known about underlying mechanisms. A possible pathway for the adverse fetal outcomes associated with PTE and PAE is the alteration of fetal autonomic nervous system development. This study assessed PTE and PAE effects on measures of fetal autonomic regulation, as quantified by heart rate (HR), heart rate variability (SD-HR), movement and HR-movement coupling in a population of fetuses at ≥34 weeks gestational age. Participants are a subset of the Safe Passage Study, a prospective cohort study that enrolled pregnant women from clinical sites in Cape Town, South Africa, and the Northern Plains region, US. PAE was defined by six levels: no alcohol, low quit early, high quit early, low continuous, moderate continuous, high continuous; while PTE by 4 levels: no smoking, quit early, low continuous, moderate/high continuous. Linear regression analyses of autonomic measures were employed controlling for fetal sex, gestational age at assessment, site, maternal education, household crowding and depression. Analyses were also stratified by sleep state (1F and 2F) and site (South Africa, N=4025, Northern Plains, N= 2466). The final sample included 6491 maternal-fetal-dyad assessed in the third trimester (35.21±1.26 [mean±SD] weeks gestation). PTE was associated with a decrease in mean HR in state 2F, in a dose dependent fashion, only for fetuses of mothers who continued smoking after the first trimester. In state 1F, there was a significant increase in mean HR in fetuses whose mother quit during the first trimester. This effect was driven by the Norther Plains cohort. PTE was also associated with a significant reduction in fetal movement in the most highly exposed group. In South Africa a significant increase in mean HR both for the high quit early and the high continuous group was observed. In conclusion, this investigation addresses a critical knowledge gap regarding the relationship between PTE and PAE and fetal autonomic regulation. We believe these results can contribute to elucidating mechanisms underlying risk for adverse outcomes.